Services and attitudes to people living with HIV/AIDS among college students in Dar-es-Salaam, Tanzania - Maswanya, E.; Brown, Graham; Merriman, Gareth (East African Public Health Association, 2009)
OBJECTIVES: The objective of this study was to evaluate acceptability of voluntary testing, counselling and treatment services and attitudes towards people living with HIV/AIDS from young people's point of view. METHODS: Qualitative study (face-to-face interviews in which tapes were used) were carried out in 20 interviewed college students aged between 19-24 years of both sexes based in Dar-es-Salaam, Tanzania.RESULTS: Results showed that voluntary counselling and testing services were limited in the study area at the time of study. Participants complained of unfriendly services and unco-operative staff, poor counselling services and shortage of facilities and staff. There was fear of HIV/AIDS related stigma toward people living with HIV and AIDS, thus fostering stigma and isolation against them. Results further demonstrate that HIV/AIDS related stigma is still a very serious problem in Tanzania. Lack of HIV/AIDS related knowledge and the life-threatening character of the disease were seen as the most important determinants of AIDS-related stigma. The main benefit to go for VCT was 'knowing your status before marriage', whereas main barriers for testing were 'fear of being stigmatised' and 'fear of knowing your HIV positive status'. CONCLUSION: The results suggest that there is need of VCT specific intervention programs for young people in colleges in Tanzania to emphasize of importance of VCT services and HIV/AIDS education program to educate students' understanding of people living with HIV/AIDS, thus reducing stigma towards people living with HIV/AIDS.